Hemin impairs resolution of inflammation via microRNA‐144‐3p‐dependent downregulation of ALX/FPR2. Issue 1 (30th November 2018) - Sun, Guixiang; Lu, Yao; Zhao, Lu; Xia, Wenjun; Zhang, Han; Wang, Linfeng; Zhang, Linjing; Wen, Aiqing
Abstract : BACKGROUND: The pathomechanisms of complications due to blood transfusion are not fully understood. Elevated levels of heme derived from stored RBCs are thought to be associated with transfusion reactions, especially inflammatory responses. Recently, the proinflammatory effect of heme has been widely studied. However, it is still unknown whether heme can influence the resolution of inflammation, a key step of inflammatory response. STUDY DESIGN AND METHODS: A murine model of self‐limited peritonitis was used, and resolution was assessed by resolution indices. Western blot, quantitative reverse transcriptase polymerase chain reaction, chemotaxis assay, luciferase reporter assay, and lentivirus infections were used to investigate possible mediating mechanisms in neutrophils. RESULTS: The administration of hemin by intraperitoneal injection significantly increased the leukocyte infiltration and prolonged the resolution interval by approximately 7 hours in mouse peritonitis. In vitro, hemin significantly downregulated ALX/FPR2 protein levels (p < 0.05), a key resolution receptor, leading to the suppression of proresolution responses triggered by the proresolution ligand resolvin D1. Subsequently, miR‐144‐3p, selected by prediction databases, was found to be significantly upregulated by hemin (p < 0.05). The inhibition of miR‐144‐3p attenuated the inhibitory effect of hemin on lipoxin A4 receptor (ALX)/formyl peptide receptor 2 (FPR2) protein expression (p < 0.05). Luciferase reporter assay confirmed that miR‐144‐3p directly bound ALX/FPR2 3′‐UTR. MiR‐144‐3p overexpression significantly downregulated ALX/FPR2 protein levels, whereas miR‐144‐3p inhibition led to a significant increase in ALX/FPR2 (p < 0.05). CONCLUSION: Our results suggest that hemin prolongs resolution in self‐limited inflammation, and this action is associated with downregulation of ALX/FPR2 mediated by hemin‐induced miR‐144‐3p. These findings demonstrate a novel mechanism of hemin derived from stored RBCs for inflammatory response.